Differentiation of Human Adipose Derived Stem Cells into Smooth Muscle Cells Is Modulated by CaMKIIγ - Kaisaier Aji; Munila Maimaijiang; Abudusaimi Aimaiti; Mulati Rexiati; Baihetiya Azhati; Hamulati Tusong; Lei Cui (Stem Cells International)
The multifunctional Ca2+/calmodulin-dependent protein kinase II (CaMKII) is known to participate in maintenance and switches of smooth muscle cell (SMC) phenotypes. However, which isoform of CaMKII is involved in differentiation of adult mesenchymal stem cells into contractile SMCs remains unclear. In the present study, we detected γ isoform of CaMKII in differentiation of human adipose derived stem cells (hASCs) into SMCs that resulted from treatment with TGF-β1 and BMP4 in combination for 7 days. The results showed that CaMKIIγ increased gradually during differentiation of hASCs as determined by real-time PCR and western blot analysis. The siRNA-mediated knockdown of CaMKIIγ decreased the protein levels and transcriptional levels of smooth muscle contractile markers (a-SMA, SM22a, calponin, and SM-MHC), while CaMKIIγ overexpression increases the transcriptional and protein levels of smooth muscle contractile markers. These results suggested that γ isoform of CaMKII plays a significant role in smooth muscle differentiation of hASCs.